1H-MRS metabolites and rate of β-amyloid accumulation on serial PET in clinically normal adults. (26th September 2017) - Nedelska, Zuzana; Przybelski, Scott A.; Lesnick, Timothy G.; Schwarz, Christopher G.; Lowe, Val J.; Machulda, Mary M.; Kremers, Walter K.; Mielke, Michelle M.; Roberts, Rosebud O.; Boeve, Bradley F.; Knopman, David S.; Petersen, Ronald C.; et al.
Abstract : Objective: To assess whether noninvasive proton magnetic resonance spectroscopy ( 1 H-MRS) tissue metabolite measurements at baseline can predict an increase in the rate of β-amyloid (Aβ) accumulation on serial PET in clinically normal (CN) older adults. Methods: Consecutive participants aged 60 years and older (n = 594) from the Mayo Clinic Study of Aging who were CN at baseline and who underwent 1 H-MRS from the posterior cingulate voxel and longitudinal 11 C-Pittsburgh compound B (PiB)–PET were included. The rate of Aβ accumulation by serial cortical PiB standardized uptake value ratios was estimated as a function of baseline 1 H-MRS metabolite ratios and time using mixed-effect models adjusted for age, sex, and APOE ε4. Effect of APOE ε4 on the relationship between baseline MRS and an increased rate of Aβ accumulation was also assessed. Results: Among all participants, a higher myo-inositol (mI)/creatine ( p = 0.011) and a lower N -acetylaspartate/mI ( p = 0.006) at baseline were associated with an increased Aβ accumulation over time after adjusting for age, sex, and APOE ε4. APOE ε4 did not modify the association of baseline 1 H-MRS metabolite ratios and rate of Aβ accumulation. However, APOE ε4 carriers accumulated Aβ faster than noncarriers regardless of the baseline Aβ load ( p = 0.001). Conclusion: Among CN older adults, early metabolic alterations on 1 H-MRS and APOE ε4 status are independently associated with an increased rate of Aβ accumulation. Our findings could have important implications for early diagnosis and identification of individuals for secondary prevention trials, because an increased rate of Aβ accumulation in CN older adults may confer a higher risk for cognitive decline and mild cognitive impairment.